Strategi Pengembangan Ekowisata Mangrove Berbasis Daya Dukung Kawasan di Kelurahan Oesapa Barat Kecamatan Kelapa Lima Kota Kupang: Mangrove Based Ectourism Development Strategy Potential Carrying Capabilities of The Area in West Oesapa Village Kelapa Lima District, Kupang City (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Mangrove ecotourism in West Oesapa village is ecotourism located in a densely populated area, so if this ecotourism is not managed properly it will have fatal consequences for the mangrove ecosystem. This research aims to determine the suitability of mangrove ecotourism resources and also the carrying capacity of mangrove areas as well as the development strategies so that they can be taken into consideration by stakeholders in making future management policies for mangrove ecotourism. The data collection method was carried out by direct observation, interviews and also collecting data from previous research conducted in the research area, then to formulate a strategy for developing mangrove ecotourism using SWOT analysis. The results of the data analysis of the suitability of mangrove ecotourism resources are at a level corresponding to a value of 2.24 with the number of visitors in the ecotourism area according to the calculation of the area's carrying capacity of 84 people per day with an operational time of the tourist area of ​​8 hours per day. The direction for developing mangrove ecotourism is to implement a diversification strategy, meaning using existing strengths to take advantage of long-term opportunities to cover weaknesses (threats).